2023
DOI: 10.18517/ijaseit.13.5.19023
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition on Facial Expression and Voice: Analysis and Discussion

Kok-Why Ng,
Yixen Lim,
Su-Cheng Haw
et al.

Abstract: Emotion plays an important role in our daily lives. Emotional individuals can affect the performance of a company, the harmony of a family, the wellness or growth (physical, mental, and spiritual) of a child etc. It renders a wide range of impacts. The existing works on emotion detection from facial expressions differ from the voice. It is deduced that the facial expression is captured on the face externally, whereas the voice is captured from the air passes through the vocal folds internally. Both captured ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Gray & Wegner, 2012;Huebner, 2010;Kramer et al, 2018;Searle, 1980). AI can recognize and mimic human emotions using techniques such as convolutional neural networks for facial expression analysis (Kajale et al, 2023;Ng et al, 2023). However, AI's identification and expression of emotions is based on pattern recognition and data analysis rather than genuine emotional comprehension through "the experience of a sentient being" (Sajjad et al, 2023, p. 820).…”
Section: Ai Management and Benevolencementioning
confidence: 99%
See 2 more Smart Citations
“…Gray & Wegner, 2012;Huebner, 2010;Kramer et al, 2018;Searle, 1980). AI can recognize and mimic human emotions using techniques such as convolutional neural networks for facial expression analysis (Kajale et al, 2023;Ng et al, 2023). However, AI's identification and expression of emotions is based on pattern recognition and data analysis rather than genuine emotional comprehension through "the experience of a sentient being" (Sajjad et al, 2023, p. 820).…”
Section: Ai Management and Benevolencementioning
confidence: 99%
“…We did not directly measure the capability of AI management to experience emotions in our studies. Although prior work has shown that AI is unable to experience emotions and that individuals recognize this limitation (Bigman & Gray, 2018;Kajale et al, 2023;Ng et al, 2023;Sajjad et al, 2023), researchers have begun to explore factors, such as anthropomorphism, that might increase the perceived emotional experience of AI. Although some studies suggest that making AI managers more humanlike might increase trust, others suggest that attempting to make them too humanlike can lead to backlash (Mori et al, 2012;Schroeder & Epley, 2016;Schroeder & Schroeder, 2018).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation